Optimizing adjuvant strategies for sevoflurane-related emergence delirium: a Bayesian network meta-analysis in pediatric surgery - Zhang, Chun-Jin; Chen, Hong; Zou, Kang; Qu, Xi (Frontiers in Pharmacology, 2025)
ObjectiveTo compare the efficacy of different anesthetic adjuvants combined with sevoflurane across specific surgical sites using a Bayesian network meta-analysis.MethodsA systematic review was conducted, following PRISMA guidelines, including 100 randomized controlled trials (RCTs) involving 8,800 pediatric patients undergoing various surgeries. The network meta-analysis evaluated 22 drug interventions, with log risk ratios (logRR) and Surface Under the Cumulative Ranking (SUCRA) probabilities calculated for each drug or combination.ResultsAmong all interventions, dexmedetomidine combined with alfentanil was the most effective in reducing ED risk for tonsillectomy/adenoidectomy, achieving a SUCRA ranking of 94.63% (logRR = −2.82). For ophthalmic surgery, propofol and midazolam showed the highest efficacy (logRR = −1.83, SUCRA: 86.03%). Dexmedetomidine combined with midazolam was the optimal combination for inguinal hernia/hypospadias (logRR = −2.16, SUCRA: 81.73%) and dental/oral repairs (logRR = −1.83, SUCRA: 94.85%). For cleft lip/palate repair, dexmedetomidine alone showed significant efficacy (logRR = −1.65, SUCRA: 89.15%). In myringotomy/cochlear implantation, fentanyl was the most effective adjuvant (logRR = −1.17, SUCRA: 80.02%).ConclusionTargeted use of dexmedetomidine-based combinations was found to be particularly effective across various surgeries, while fentanyl and propofol-midazolam combinations excelled in specific contexts. This study underscores the importance of tailoring anesthetic adjuvant strategies to specific surgical sites to reduce the risk of ED in pediatric patients, and provides a valuable reference for optimizing anesthetic care in this vulnerable population.